Managing variability in ocean shipping - Harrison, Alan; Fichtinger, Johannes (Mcb, 2013)
Purpose – The paper aims to explore the relationship between time-related variables in global ocean transportation networks (GOTNs) and the shipper's inventory management performance. The authors modelled fill rates with daily and weekly sailings, and analysed the impact of variability on these on the shipper's inventory management system.Design/methodology/approach – The authors conducted simulation modelling of the above variables, and supplemented these by means of interviews with executives in a number of liner operators, 3PLs, freight forwarders and a large automotive shipper.Findings – Improvements in variability have different impacts, depending on the source of the variability and the frequency of the shipments. The highest inventory reduction potential arises from a combination of high reliability and improved frequency.Practical implications – The paper demonstrates the potential advantages of reduced variability and improved frequency of sailings. Port-to port (P2P) has been positioned in the context of door-to-door (D2D) supply chain movements.Originality/value – The paper develops clear quantitative analyses of time-based factors in operating GOTNs.
Keywords: Freight forwarding; Marine transport; Supply chain management; Global ocean transportation; Variability of transit times; Inventory management; Simulation; Supply chain performance